2024
DOI: 10.3390/ijms25052911
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin in Cancer and Inflammation: An In-Depth Exploration of Molecular Interactions, Therapeutic Potentials, and the Role in Disease Management

Dong-Oh Moon

Abstract: This paper delves into the diverse and significant roles of curcumin, a polyphenolic compound from the Curcuma longa plant, in the context of cancer and inflammatory diseases. Distinguished by its unique molecular structure, curcumin exhibits potent biological activities including anti-inflammatory, antioxidant, and potential anticancer effects. The research comprehensively investigates curcumin’s molecular interactions with key proteins involved in cancer progression and the inflammatory response, primarily t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 153 publications
(191 reference statements)
0
1
0
Order By: Relevance
“…To further investigate the anti-inflammatory effects of echinatin in MH-S cells, we measured the amount of NO and PGE 2 in MH-S cells. Curcumin is a natural chalcone compound with proven anti-inflammatory activity, therefore, we used curcumin as a positive control [ 24 26 ]. The results showed that echinatin markedly inhibited the production of NO in LPS-stimulated MH-S cells in a dose-dependent manner ( Fig 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate the anti-inflammatory effects of echinatin in MH-S cells, we measured the amount of NO and PGE 2 in MH-S cells. Curcumin is a natural chalcone compound with proven anti-inflammatory activity, therefore, we used curcumin as a positive control [ 24 26 ]. The results showed that echinatin markedly inhibited the production of NO in LPS-stimulated MH-S cells in a dose-dependent manner ( Fig 1C ).…”
Section: Resultsmentioning
confidence: 99%